THYMIC STROMAL LYMPHOPOIETIN: THE FUNCTIONAL IMPLICATIONS OF THE TSLP GENE POLYMORPHISM RS1837253 IN ALLERGIC ASTHMA - Hanna, Raphael (My University, 2017)
Thymic stromal lymphopoietin (TSLP) is a regulator of Th2 immune responses and is highly implicated in the pathophysiology of asthma and allergic diseases. Although robust data is present referencing the associations of polymorphisms in the TSLP gene with the development of allergy and asthma, there is very limited information on how TSLP gene variants functionally affect downstream effector pathways with regards to disease phenotypes in the clinical setting. The overall objective of this thesis is to investigate how TSLP polymorphisms are linked to the clinical phenotypic differences including alterations in TSLP secretion and subsequent downstream cellular events. We show that polyinosinic:polycytidylic acid (polyI:C) enhanced TSLP secretion from nasal epithelial cells (NEC). To explore the potential regulatory mechanisms acting on a key variant of the TSLP gene, we investigated associations between the rs1837253 TSLP variant and transcriptional regulatory factors RIG-1 and AP-1, finding no association between levels of expression of these regulators and genotype. We also investigated ex vivo production of TSLP and downstream cytokines in nasal epithelial cells (NEC) in asthmatic and non-asthmatic individuals to outline variances in expression according to disease status and genotype. We showed that NEC derived from asthmatic individuals showed significant differences in expression in asthmatic compared to non-asthmatic individuals. Furthermore, we demonstrated that there was a difference in the expression of TSLP in the asthmatic subpopulation compared to non-asthmatics when categorized by genotype, suggesting an altered regulatory mechanism of TSLP secretion for asthmatic compared to non-asthmatic individuals.